Potential of Eucalyptus (Eucalyptus camaldulensis) essential oil to modify in vitro rumen fermentation in sheep - Attia K.; Chouchen R.; Darej C.; Moujahed N. (The value chains of Mediterranean sheep and goat products. Organisation of the industry, marketing strategies, feeding and production systems, 2016)
The current study aimed at evaluating the effects of increasing doses (0, 10, 20, 40, 80 and 120 μl/50 ml of buffered rumen fluid) of essential oil (EO) extracted from the leaves of Eucalyptus (Eucalyptus camaldulensis) on some in vitro rumen fermentation characteristics. Doses of EO were added to 0.5 g of a diet composed of 50% of rye-grass hay and 50% of concentrate. The medium of incubation consisted on ruminal liquid extracted from sheep, mixed in equal proportions with a buffer solution introduced in 100 ml glass syringes (39°C). At 24 h of incubation gas production (GP) was measured, a part of the liquid was collected for analysis of ammonia nitrogen (NH3-N) and 3 syringes were reserved to determine true organic matter degradability (TOMD).Then the partitioning factor (PF) was estimated after 24 h of incubation. Results showed that, GP was not affected at 10 μl of EO, but decreased significantly (P<0.0001) for 20, 40, 80 and 120μl doses by 16, 29.7, 46.3 and 54.5 % respectively, comparatively with the dose 0 μl. NH3-N concentration was reduced (P<0.0001) by 8.2, 18.6, 21.6 and 25 % when 20,40, 80 and 120 μl of EO were added, comparatively with dose 0 μl. TOMD values were equivalent among the doses 0, 10 and 20 μl of EO, but decreased significantly (P<0.0001) at doses 40, 80 and 120 μl, which were equivalent. The PF values were 2.93, 3.68, 3.81, 4.48, 5.26 and 7.43 for the increasing doses of EO. The only significant difference (P<0.05) was observed between doses 0μl and 120 μl. It was concluded that EO modified fermentation trends in the rumen, mainly by reducing GP and protein deamination. At low doses, TOMD seemed not to be drastically affected. In vivo studies are needed to demonstrate eventual benefits from utilization of EO by ruminant sand to situate the compromise between reducing gas emission and positive effects on digestion.
Joint Seminar of the Subnetworks on Nutrition and on Production Systems of the FAO-CIHEAM Network for Research and Development in Sheep and Goats, 2015/06/16-18, Montpellier (France)